Graptolites of the Pribylograptus leptotheca and Lituigraptus convolutus biozones of Tman (Silurian, Czech Republic) - Storch,P. (Journal of the Czech Geological Society, 1998)
The well preserved graptoloid fauna of the middle Aeronian (middle Llandovery) leptotheca and convolutus biozones comprising 60 species and subspecies is described from Svaty Jiri near Tman. The leptotheca Biozone has been introduced in the Silurian graptolite zonal scheme of the Barrandian area in place of the lower part of the convolutus Biozone of former classifications. A dominance of uniserial rastritid forms (both species and specimen abundance) is documented by quantitative analysis of bulk samples. Seven new species (Normalograptus? inornatus, Petalolithus krizi, Neolagarograptus impolitus, Monograptus respectabilis, M. dracocephalus, M. mirificus and Campograptus sanctgeorgensis) and one new genus (Neolagarograptus) are erected and ten species are left in open nomenclature. Twenty-three taxa are recorded for the first time in Bohemia.
Keywords: graptolites; Silurian; middle Llandovery; taxonomy; biostratigraphy; faunal composition